Incorporation of methylene blue and direct red 80 into thin films. - Ilisan, Honey Joy Gonzales
Layer-by-layer assembly was used to fabricate thin films of dyes and polyelectrolytes. Poly(allylamine hydrochoride) (PAH), Polyacrylic acid (PAA), poly (styre sulfonate) (PSS), Direct Red 80 (DR80) and Methylene Blue (MB) were used fort he fabrication of this thin film. The pH of dipping solutions were adjusted to pH 4, pH 7, and pH 9 to give the researcher an idea on the interactions involved in the adsorption of dyes on polyelectolytes. Desired amount of salt was added after the pH adjustment to determine the effect of ionic strength on the adsorption of polyelectrolytes. Taking the UV-Vis spectra after each bilayer of dye/polyelectrolyte system monitored the adsorption of dyes., The adsorption behavior of dyes (MB and DR80) onto polyelectrolytes with a concentration of 0.1M and 1mg/mL solution at pH 4 was determined by the UV-Vis spectrophotometer. The adsorption of the DR80 onto PAH surface obtained an increasing trend whereas MB onto PAA surface did not follow the trend. At pH 7 and pH 9 polyelectrolyte solutions, the UV-Vis showed that the adsorptions were in distended manner. Addition of salt concentration to the PAA solution decrease the viscosity of the solution. With higher salt concentration at pH 7 and pH 9, the adsorption of MB/PAA and PAH/DR80 layer were not uniform.